EU and crisis management: Afghanistan and Ukraine on social media - Pérez-Curiel, Concha; Garrote-Fuentes, Álvaro; Rivas-de-Roca, Rubén (Frontiers in Political Science, 2023)
The European Union (EU) is a very relevant actor in the political scene. The EU’s external action is inspired on the principles of peace and rule of law. However, the EU is composed by different institutions and leaders, making it difficult to find a single voice. This promotes a feeling of remoteness that threatens the legitimacy of the EU political system. In recent years, the EU has faced many internal challenges such as the refugee crisis or Brexit, but the recent events in Afghanistan and Ukraine reveal the need to further our understanding on the role of the EU as an international actor. Bearing these trends in mind, this research aims to explore the management of crisis communication by the EU leaders regarding the two most recent international events: Afghanistan in 2021 and Ukraine in 2022. Specifically, we analyze the profiles of Ursula von der Leyen (@vonderleyen), Josep Borrell (@JosepBorrellF) and Charles Michel (@eucopresident). A content analysis is manually performed on 479 tweets on military conflicts over a general sample of 661 messages. The strategies and specific topics are studied based on a pre-test. Additionally, we calculate the impact rate of the tweets. In this sense, the data were captured for a two-month period (August 15-September 15, 2021 and February 24-March 24, 2022). As results, we show the predominance of messages on the Ukraine together with a significant different action of von der Leyen in terms of strategies and employment of the tools of Twitter. Her impact rate is also higher. This study contributes to current discussions on the mission of communication to foster trust, since the anti-publicity bias of the EU requires better levels of coherence to more effectively disseminate messages.